Innovation and Marketing Activity of High Technology Companies in Business Management - Yuriy Petrovich Aniskin; Nina Konstantinovna Moiseeva; Dmitriy Borisovich Rygalin; Olga Valeryevna Sedova (International Journal of Economics and Financial Issues, 2015)
The article states the results of researching the problems related to managing business activity of high technology companies whose key components include innovation and marketing activity. These components of business activity are interrelated, because as the innovation activity increases, the need in increasing the marketing activity in order to ensure the market readiness to consuming new products grows as well. In its turn, it creates conditions for widespread output of innovations and quick return of investments. It is proposed to estimate and regulate innovation and marketing activity by using the combination of the stipulated indicators and models. In order to successfully manage innovation and marketing activity, relevant mechanisms are required. Their methodological peculiarities are described in the article.